(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Krutchenko L. V. The role of styling design in developing students’ creativity. The article reveals psychological and pedagogical bases of secondary school students’ creative activity as well as stipulates possibilities for using the process of styling design as a means of developing students’ creativity.